2012
DOI: 10.1002/hrm.21507
|View full text |Cite
|
Sign up to set email alerts
|

Human resource management and developing proactive environmental strategies: The influence of environmental training and organizational learning

Abstract: The need to implement advanced approaches to protect the environment is forcing companies to refocus their internal procedures and actions. To match employees' capabilities and the organization itself to these new requirements, the human resource management department can offer some key tools. This article analyzes whether environmental training (ET) and organizational learning (OL) positively influence the development of proactive environmental strategies (PESs) and compares the two processes, which differ in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
95
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(106 citation statements)
references
References 162 publications
3
95
1
2
Order By: Relevance
“…In this way, we are able to triangulate information related to pressures and performance (as they are asked to two respondents), whereas (according to current practices in green HRM, e.g. Vidal-Salazar et al, 2012;Martínez-del-Río, Céspedes-Lorente, & Carmona-More, 2012;Kulik, 2014) the information related to green HRM practices comes from the HR manager, who is the most knowledgeable respondent in this regard. Although the HR manager is the natural target respondent for green HRM practices, we also chose to target the supply chain (SC) function because this part of the value chain has long been subject to environmental-related pressures and managers are expected to be knowledgeable about environmental-related stakeholder pressures, as well as the firm environmental performance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, we are able to triangulate information related to pressures and performance (as they are asked to two respondents), whereas (according to current practices in green HRM, e.g. Vidal-Salazar et al, 2012;Martínez-del-Río, Céspedes-Lorente, & Carmona-More, 2012;Kulik, 2014) the information related to green HRM practices comes from the HR manager, who is the most knowledgeable respondent in this regard. Although the HR manager is the natural target respondent for green HRM practices, we also chose to target the supply chain (SC) function because this part of the value chain has long been subject to environmental-related pressures and managers are expected to be knowledgeable about environmental-related stakeholder pressures, as well as the firm environmental performance.…”
Section: Methodsmentioning
confidence: 99%
“…Green training is also shown to be the most adopted practice among green HRM practices (CIPD, 2013). Accordingly, several researchers suggested that enhancing employee environmental knowledge and skills plays a key role in improving environmental performance (Vidal-Salazar, Cordón-Pozo, & Ferrón-Vilchez, 2012;Longoni, Golini, & Cagliano, 2014). Green training increases employees' ability to recognize environmental issues (Govindarajulu and Daily, 2004), to have a deeper understanding of the complexity of environmental problems (Perron, Côté, & Duffy, 2006) …”
Section: Hp2a Green Hiring Is Positively Related To Environmental Pementioning
confidence: 99%
“…Following this paper, the study of internal business factors that facilitate the implantation of environmental practices and objectives attracted the interest of business management literature. The academic studies involved highlight the impact of factors, such as firm size [3,4], managerial attitudes [5][6][7][8], employee motivation and qualification [4,9], high-involvement work practices [10], innovation [11] or internationalization [12].…”
Section: Introductionmentioning
confidence: 99%
“…A sociedade está cada vez mais atenta às questões ambientais. A preocupação com responsabilidade social deve começar no ambiente interno, podendo trazer ganhos estratégicos aos gestores (Burke & Longsdon, 1996;Banerjee, 2002;Gomes, 2010;Porter & Kramer, 2011;Dicle & Kose, 2014;Vidal-Salazar et al, 2012). Grande parte do trabalho relativo à transição para a efetiva sustentabilidade ambiental demandará investimentos em infraestrutura e novos projetos para saúde e educação (Pnud, 2015).…”
Section: A Cultura Da Sustentabilidade Nas Organizaçõesunclassified
“…Para que a organização desenvolva estratégias sustentáveis, é necessário que tenha abertura à inovação (Vidal-Salazar et al, 2012). A Gestão do Conhecimento, como processo de aquisição, recuperação e proteção dos saberes organizacionais (Benjamins, 2013;Gaines, 2013;AussenacGilles & Gandon, 2013), auxilia a difusão da cultura da sustentabilidade, uma vez que se trata de uma abordagem resoluta e sistemática a fim de assegurar a plena utilização, não somente da base de conhecimento da organização, mas também das competências e habilidades das pessoas, dos pensamentos, das inovações e ideias, com o propósito de aumentar os níveis de eficiência e eficácia organizacionais (Dalkir, 2005).…”
Section: ____________________________________________________________unclassified